Effect of Composting on the Behavior of Polyolefin Films - A True-to-Life Experiment - Vargha, Viktória; Csoknyay, Tamás; Kárpáti, Levente; Bordós, Gábor; Hartman, Mátyás; Háhn, Judit; Korecz, László; Szarka, Györgyi; László, Zsolt; Kelemen, Ottó; Szoboszlay, Sándor (Journal of Applied Solution Chemistry and Modeling, 2016)
Commercial polypropylene (PP), high-, medium- and low density polyethylene (HDPE, MDPE, LDPE) films, as well as MDPE films containing pro-oxidative additives and thermoplastic starch (TPS) were composted for six weeks together with biologically degradable films, such as poly (lactic acid) (PLA), Ecovio (BASF), Mater Bi(Novamont) and cellophane. Visual appearance of the polyolefin-based films did not change significantly, while the biologically degradable films fell apart. Thickness and mechanical properties of the polyolefin-based films also did not vary significantly after composting. The thickness of the degradable films however increased due to biofilm formation and finally decreased due to biodegradation, and their mechanical properties drastically dropped. FTIR proved the formation of carbonyl absorption of commercial and of the additive-containing films respectively) after composting due to oxidation. The FTIR-spectrum of the biodegradable films showed drastic change after composting. Formation of free radicals was detectable by ESR-spectroscopy, if pro-oxidative additive containing MDPE film was exposed for one week to sunlight, and the intensity of free radical formation increased after composting. The number-average molecular mass of MDPE films containing pro-oxidative additives decreased, low molecular mass fractions appeared and polydispersity increased after composting. Commercial polyolefin films were covered by microorganisms much more densly than films containing pro-oxidative additives detected by SEM. Even TPS did not increase the quantity of microorganisms. Biodegradable films were densly covered by microorganisms of different types and they became porous and holes were observable on their surface. It can be concluded that composting had no significant effect on the behaviour of the commercial PP and PE films. Signs of initial degradation were observable on MDPE films with pro-oxidative additives and TPS after 6 weeks composting, although it cannot be considered as biological degradation. Non of the tested polyolefin films suffered such degree of degradation in compost, as the biologically degradable films. It may be concluded that polyolefin films neither degrade in compost nor they undergo biodegradation.